Can We Accurately Predict the Quadruple Hamstring Graft Diameter From Preoperative Magnetic Resonance Imaging?. Issue 3 (26th March 2019) - Vardiabasis, Nicolas; Mosier, Brian; Walters, Jason; Burgess, Aaron; Altman, Greg; Akhavan, Sam
Background: Anterior cruciate ligament (ACL) reconstruction with a quadruple hamstring (QH) autograft is a widely utilized procedure with good outcomes. A graft diameter less than 8 mm, however, has been associated with higher revision rates. Accurately determining the diameter of the hamstring tendon preoperatively can help surgeons plan accordingly. Purpose/Hypothesis: The purpose of our study was to determine whether QH graft size can be reliably predicted from preoperative magnetic resonance imaging (MRI) measurements. We hypothesized that we can achieve a high predicted QH graft size correlation with regard to preoperative and intraoperative measurements. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: We evaluated patients undergoing ACL reconstruction using QH autografts. At the time of surgery, the semitendinosus tendon (ST) and gracilis tendon (GT) were harvested and sized and then sized as a QH graft. Preoperative individual ST and GT sizes were determined from T2-weighted fat-saturated MRI at 3 cm above the joint line using correlating axial and coronal images. We then used a predictive chart to predict what the size of the QH graft would be and compared this with the actual measurements. Pearson correlation coefficients between predicted and actual graft sizes were calculated. Results: The predicted GT graft size was within 0.5 mm of the actual size in 45 of 60 (75%) patients and within 1 mm of the actual graft size in 59 of 60 (98%) patients. The predicted GT graft size from MRI measurements correlated with the actual GT graft size ( r = 0.62, P < .00001). The predicted ST graft size was within 0.5 mm of the actual size in 45 of 60 (75%) patients and within 1 mm of the actual graft size in 56 of 60 (93%) patients. The predicted ST graft size from MRI measurements correlated with the actual ST graft size ( r = 0.71, P < .00001). The predicted QH graft size was within 0.5 mm of the actual size in 52 of 60 (87%) patients and within 1 mm of the actual graft size in 60 of 60 (100%) patients. The predicted QH graft size from MRI measurements correlated with the actual QH graft size ( r = 0.81, P < .00001). Conclusion: The current technique can reliably predict the size of a QH graft within 1 mm of the final graft size.